2010
DOI: 10.1007/s12042-010-9056-z
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Gene Expression in the Nematode Resistant Wild Peanut Relative, Arachis stenosperma, in Response to Challenge with Meloidogyne arenaria

Abstract: Peanut (Arachis hypogaea) is amongst the most important legume crops in the world. One of its main yield constraints is the root-knot nematode Meloidogyne arenaria. A number of wild Arachis species, including A. stenosperma, are resistant to nematodes, and are a potential source of new resistance alleles for cultivated peanut. Using in silico subtraction of ESTs and macroarray analysis, we identified genes differentially expressed in A. stenosperma roots during its resistance response to M. arenaria. The three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
(82 reference statements)
7
19
0
Order By: Relevance
“…However, throughout the assay, an increase in expression was observed, and 79% of the genes were upregulated at 9 DAI. These results agree with the expression profiles reported during root-knot nematode infection in Arachis (Guimarães et al 2010;Tirumalaraju et al 2011) and other plants, such as rice (Kyndt et al 2012), Arabidopsis (Jammes et al 2005;Barcala et al 2010), tomato (Portillo et al 2013) and cowpea (Das et al 2010). These studies reported gene repression or constant expression at early stages of nematode-plant interaction, followed by a trend towards an increasing number of upregulated genes in both compatible and incompatible interactions.…”
Section: Gene Expression Profilessupporting
confidence: 90%
See 4 more Smart Citations
“…However, throughout the assay, an increase in expression was observed, and 79% of the genes were upregulated at 9 DAI. These results agree with the expression profiles reported during root-knot nematode infection in Arachis (Guimarães et al 2010;Tirumalaraju et al 2011) and other plants, such as rice (Kyndt et al 2012), Arabidopsis (Jammes et al 2005;Barcala et al 2010), tomato (Portillo et al 2013) and cowpea (Das et al 2010). These studies reported gene repression or constant expression at early stages of nematode-plant interaction, followed by a trend towards an increasing number of upregulated genes in both compatible and incompatible interactions.…”
Section: Gene Expression Profilessupporting
confidence: 90%
“…Basic helix-loop-helix (bHLH) proteins constitute one of the largest TFs families in Arabidopsis (Heim et al 2003). In this study, the significant upregulation of an A. stenosperma homolog (AsbHLH) in infected roots corroborates previous macroarray data ( Guimarães et al 2010). Some of these bHLH TFs form clusters regulating specific jasmonic acid (JA)-dependent responses, which modulate processes including defence against pathogens (Fernandez-Calvo et al 2011).…”
Section: Transcriptional Regulationsupporting
confidence: 88%
See 3 more Smart Citations